Atyrau region current energy status - Sabirova, R.K.; Karamuldina, А.А.; Tlepova , G.B. (BUKETOV BUSINESS REVIEW, 2017)
This studyis devoted to the researchof the current state of Atyrauregion’s energy and efficient energy supply, to use in everyday life by producing alternative sources of energy, which is valuable in terms of technological innovation in the energy industry in the region. Currently and in the foreseeable future the most important energy resources will remain hydrocarbons, because oil and gas are the raw materials which determines the kind of fuel, mineral and synthetic materials. Because of these properties, they will be stable and long-term in leading the global energy balance. According to the most expert estimates, the share of hydrocarbons in the nearest future will not fall below 80 % and the highest demand for this resource leads to an increasing transformation of international relations from the geopolitical territorial claims to control over zones of oil and gas deposits and transport routes. Nowadays electric power complex is characterized as a highly capital-intensive and initiative. Therefore, a set of measures for the development of electric power is required, so that it won’t be the «bottleneck» in the economy, stopping the development of the region and the country at all and to be competitive in terms of integration into the world economy.